31P Magnetic resonance spectroscopic imaging with polarisation transfer of phosphomono- and diesters at 3 T in the human brain: relation with age and spatial differences - Wijnen, J. P.; Scheenen, T. W. J.; Klomp, D. W. J.; Heerschap, A. (NMR in biomedicine, 2010)
Tissue levels of the compounds phosphocholine (PC), phosphoethanolamine (PE), glycerophosphocholine (GPC) and glycerophosphoethanolamine (GPE) can be studied by in vivo 31P MRS. However, the detection of the signals of these compounds suffers from low sensitivity and contamination by underlying broad resonances of other phosphorylated compounds. Improved sensitivity without this contamination can be achieved with a method for optimal polarisation transfer of 1H to 31P spins in these molecules, called selective refocused insensitive nuclei‐enhanced polarisation transfer (sRINEPT). The aim of this study was to implement a three‐dimensional magnetic resonance spectroscopic imaging (MRSI) version of sRINEPT on a clinical 3 T magnetic resonance system to obtain spatially resolved relative levels of PC, PE, GPC and GPE in the human brain as a function of age, which could be used as a reference dataset for clinical applications. Good signal‐to‐noise ratios were obtained from voxels of 17 cm3 of the parietal and occipital lobes of the brain within a clinically acceptable measurement time of 17 min. Eighteen healthy subjects of different ages (16–70 years) were examined with this method. A strong inverse relation of the PE/GPE and PC/GPC ratios with age was found. Spatial resolution was sufficient to detect differences in metabolite ratios between white and grey matter. Moreover, we showed the feasibility of this method for clinical use in a pilot study of patients with brain tumours. The sRINEPT MRSI technique enables the exploration of phospholipid metabolism in brain diseases with a better sensitivity than was possible with earlier 31P MRS methods. Copyright © 2010 John Wiley & Sons, Ltd. We acquired 31P MRSI with polarisation transfer of the signals of phosphomono and diesters only of 17cc voxels in the brain of different ages within a clinically acceptable measurement time of 17 minutes. A strong inverse relation of the PE/GPE and PC/GPC ratio with age was found. Spatial resolution was sufficient to detect differences in metabolite ratios between white and gray matter.